The photodynamic activities of the gold nanoparticle conjugates of phosphorus(V) and gallium(III) A3meso-triarylcorroles. (October 2021) - Soy, Rodah C.; Babu, Balaji; Mack, John; Nyokong, Tebello
Abstract: The synthesis and characterization of series of P(V) and Ga(III) A3 triarylcorrole complexes with 4-methylthiophenyl (2a, 3a ), thien-3-yl (2b, 3b ) and thien-2-yl (2c, 3c ) meso -groups are reported along with the physicochemical and photodynamic activity properties of the dyes and their gold nanoparticle (AuNP) conjugates. The Ga(III) corrole series have lower fluorescence quantum yields and higher singlet oxygen quantum yields than the analogous P(V) complexes. Upon conjugation to AuNPs, the fluorescence quantum yields of the P(V) and Ga(III) corroles decrease, while the singlet oxygen quantum yields increase due to an external heavy atom effect. The P(V) and Ga(III) corroles exhibit relatively low in vitro dark cytotoxicity, which was further enhanced upon conjugation to AuNPs. The P(V) complexes and their AuNP conjugates display more favorable PDT activity properties upon illumination with a Thorlabs 625 nm light-emitting diode (288 J cm −2 ) with phototoxicity indices > 18.5 and 20.8, respectively, for the meso -thienyl-substituted 2b -AuNP and 2c -AuNP conjugates. Optical spectroscopy analyses demonstrate that this can be attributed to there being significantly less aggregation due to the presence of two trans -hydroxy axial ligands. Graphical abstract: Image 1 Highlights: P(V) and Ga(III) complexes of trithien-2-yl- and trithien-3-ylcorrole were prepared. Properties were compared to corrole complexes with meso -4-methylthiophenyl rings. Gold nanoparticle conjugates of the P(V) and Ga(III) complexes were prepared. Photodynamic activities against MCF-7 breast cancer cells were assessed. Low IC50 values (<10 μg/mL) were further enhanced by nanoparticle conjugation.